Retro-prospective review of abscess epidemiology and its management in Western subdivisional hospitals in Fiji - Bancod, Robert; Gogoi, Abhijit; Buenafe, Dennis; Nadan, Muni; Radhika, Sanam; Pal, Ronesh (International Surgery Journal, 2025)
Background: Abscesses, localized collections of pus resulting from bacterial infections, pose significant challenges to patient care. They are categorized into internal and cutaneous abscesses, with internal abscesses being more severe and harder to diagnose. Limited data exists on the epidemiology and management of abscesses in Fiji, particularly in subdivisional hospitals. This study aims to investigate the prevalence, anatomical distribution, demographic trends, and etiological factors of abscesses in subdivisional hospitals in Fiji’s Western division. Additionally, it seeks to analyze management strategies and outcomes to inform improvements in clinical practice. Methods: A retrospective study was conducted from January 2020 to September 2022, analyzing patient data from four subdivisional hospitals-Rakiraki, Tavua, Nadi, and Sigatoka. The study utilized both qualitative and quantitative methods, with MBBS students collecting data under medical supervision. Statistical analyses were performed to assess demographic trends, anatomical sites, and microbiological findings. Results: A total of 1,160 abscess cases were recorded, with Sigatoka hospital reporting the highest number (588 cases). Pediatric patients (ages 0-20) were the most affected, with a male predominance. The most common anatomical sites included the scalp, abdomen, head and neck, limbs, and gluteal region. S. aureus was the predominant pathogen, followed by S. pyogenes and E. histolytica. Management strategies involved incision and drainage (I and D), antibiotic therapy, and wound care, with variations based on abscess location and severity. Conclusions: The study highlights a high prevalence of abscesses in pediatric and male populations in Fiji’s Western division. The identification of bacterial and parasitic pathogens underscores the need for targeted antibiotic and antiparasitic treatments. Findings emphasize the importance of public health interventions, improved hygiene practices, enhanced diagnostic capabilities, and antibiotic stewardship programs to optimize patient outcomes and reduce abscess-related morbidity in the region.